Synthetic Biology for Bio-Control: A Mini-Review - Kemal, Rahmat Azhari; Islamiah, Paramita W.N.; Lusiany, Tina (Proceeding International Conference on Global Resource Conservation, 2015)
Biomolecular systems and cellular capabilities can be engineered by synthetic biology. One of its wide applications is for bio-control. Several teams competing in the International Genetically Engineered Machine (iGEM) competition have utilized the potency of synthetic biology for pest control. Some of their ideas are highlighted in this review. Taking advantages from Indonesiaâs rich biodiversity, those ideas can be expanded. Bio-control using E. coli expressing pheromone biosynthesis activating neuropeptide (PBAN) from rice yellow stem borer (Scirpophaga incertulas) can be used to control that pest. The adapted ideas can serve as starting points for research and implementation of bio-control in Indonesia.Keywords: Bio-control, biodiversity, iGEM, Indonesia, synthetic biology